Letter (copy) : Basque Children - Tewson, Vincent
1946-10-02 038-0013-001 Secretary's. HVT/EK/1191. 2nd October, 1946. Mr. D.R. Grenfell, C.B.E., M.P., "Ardwyn", Carnglas Road, Sketty, Swansea, Glam. Dear Mr. Grenfell, Basque Children. I have your letter, together with enclosures, in connection with one of the Basque children. I am passing the communication to the appropriate quarter in the hope that enquiries can be made. Yours sincerely, Acting General Secretary. PTO 292/946/38/13(I)